Reactive oxygen species-responsive dexamethasone-loaded nanoparticles for targeted treatment of rheumatoid arthritis via suppressing the iRhom2/TNF-α/BAFF signaling pathway. (February 2020) - Ni, Rongrong; Song, Guojing; Fu, Xiaohong; Song, Ruifeng; Li, Lanlan; Pu, Wendan; Gao, Jining; Hu, Jun; Liu, Qin; He, Fengtian; Zhang, Dinglin; Huang, Gang
Abstract: Rheumatoid arthritis (RA) is an immune-mediated inflammatory disease that results in synovitis, cartilage destruction, and even loss of joint function. The frequent and long-term administration of anti-rheumatic drugs often leads to obvious adverse effects and patient non-compliance. Therefore, to specifically deliver dexamethasone (Dex) to inflamed joints and reduce the administration frequency of Dex, we developed Dex-loaded reactive oxygen species (ROS)-responsive nanoparticles (Dex/Oxi-αCD NPs) and folic acid (FA) modified Dex/Oxi-αCD NPs (Dex/FA-Oxi-αCD NPs) and validated their anti-inflammatory effect in vitro and in vivo . In vitro study demonstrated that these NPs can be effectively internalized by activated macrophages and the released Dex from NPs significantly downregulated the expression of iRhom2, TNF-α, and BAFF in activated Raw264.7. In vivo experiments revealed that Dex/Oxi-αCD NPs, especially Dex/FA-Oxi-αCD NPs significantly accumulated at inflamed joints in collagen-induced arthritis (CIA) mice and alleviated the joint swelling and cartilage destruction. Importantly, the expression of iRhom2, TNF-α, and BAFF in the joint was inhibited by intravenous injection of Dex/Oxi-αCD NPs and Dex/FA-Oxi-αCD NPs. Collectively, our data revealed that Dex-loaded ROS-responsive NPs can target inflamed joints and attenuate arthritis, and the 'iRhom2-TNF-α-BAFF' pathway plays an important role in the treatment of RA with the NPs, suggesting that this pathway may be a novel target for RA therapy.